Fraud Reporting: An Experimental Examination of the Effect of Security and Financial Incentives on Trust in Whistleblowing Hotlines - Priyastiwi, Priyastiwi; Setyowati, Hasanah (The Indonesian Journal of Accounting Research, 2025)
Fraud reporting is a key element of effective corporate governance. This study empirically examines the effect of security and financial incentives on trust in whistleblowing channels and the intention to report fraud in government organizations. This study uses an internet-based experiment involving employees of government and private organizations. To test the hypothesis constructed, an analysis of variance is used. The study results show that greater channel security is associated with higher whistleblowing intentions. However, security does not affect the reporter's trust. The study also shows that financial incentives affect reporting trust and intent. The results also show that the effect of financial incentive moderation is significantly more substantial when the security of the reporting channel is low. This suggests that financial incentives can be an effective driver for organizational trust, resulting from the support of a security channel environment for whistleblowers. In a situation where reporting channel security is low, financial incentives also affect trust. The results of this study provide a new perspective on the effectiveness of fraud reporting from an organizational perspective. Research can provide theoretical support for the claim that financial incentives will increase trust when they do not yet believe that reporting channels are secure. The results of the study can inform the decision to provide financial incentives, while accounting for the ethical and practical sacrifices inherent in such decisions.